Scientific Mapping of Digital Entrepreneurship: Trends, Gaps, and Future Research Directions - Christina, Christina; Siswanto, Bambang (AIBPM Publisher, 2025)
This study investigates the rapid growth of digital entrepreneurship research from 2019 to 2024, driven by technological advancements and the increasing relevance of digital platforms. Using bibliometric analysis, the study maps the intellectual landscape of the field by identifying key themes, leading authors, influential journals, and productive institutions. The findings reveal three major thematic clusters: Business Transformation, Digital Innovation, and Inclusive Entrepreneurship, emphasizing the impact of digital technologies on business models, innovation, and economic inclusion. The role of small and medium-sized enterprises (SMEs) is highlighted as increasingly central in the global digital ecosystem. A steady increase in publications and citations is observed, with journals such as Technological Forecasting and Social Change and Journal of Business Research shaping the discourse. The study recommends future research to focus on digital platforms, business model innovation, and supportive policy and infrastructure, underscoring the transformative potential of digital entrepreneurship in fostering inclusive and sustainable development.